Désiré Based on a Play by Sacha Guitry - Guitry, Sacha; Benoit, Georges; Delubac, Jacqueline; Baumer, Jacques (Sacha Guitry: L'âge d'or (1936-1938), 2012)
Sacha Guitry exchanges his usual top hat for a uniform in "Désiré", playing a cavalier valet embroiled in an awkward flirtation with his new employer (played by the actor-director’s real-life wife, Jacqueline Delubac), who is involved with a stuffy politician. A carefree class farce filled with memorable supporting characters, "Désiré" blurs the distinction between upstairs and downstairs ... Sacha Guitry was once a household name. Something of a Gallic Noël Coward, this disarming, multitalented artist served up some of 1930s French cinema’s tastiest dishes. The son of a beloved theater actor, Guitry was devoted to the footlights, first turning to the silver screen only as a way of bringing his plays to a wider audience. His films were anything but stage-bound, however: often the director, writer, and star of his popular movies, Guitry brought a witty inventiveness to the cinema and deployed radical techniques with such aplomb and control that he’s considered one of the medium’s first complete auteurs. [www.criterion.com]